Exhaustivity and homogeneity effects with distributive‐share markers: Experimental evidence from Serbian po. (21st November 2021) - Bosnić, Ana; Demirdache, Hamida; Spenader, Jennifer
Abstract: There are two competing approaches to the semantics of distributive‐share markers: they are either universal distributive quantifiers over events or are merely event‐plurality markers. To address this debate, we present new conclusions based on novel experiments with Serbian transitive sentences in which the distributive‐share marker po was attached to the direct object. The first two experiments investigated exhaustivity effects in transitive sentences with po, while the third experiment probed homogeneity effects across three types of negative transitive sentences: with po marking the object, with the distributive‐key quantifier svaki ('every') in subject position, and with neither. If po is a universal quantifier, then it should enforce exhaustive distribution over a distributive key and remove homogeneity effects in negative sentences with a definite subject. If instead po is an event‐plurality marker with no universal quantificational force, then it should neither enforce exhaustive distribution nor remove homogeneity effects in negative sentences with a definite subject. We conclude that there are two populations of Serbian speakers with systematic patterns of interpretation: one population interprets po as a universal quantifier and one population interprets po as an event‐plurality marker. We conjecture that this population split might reflect an ongoing diachronic change in the semantic import of the distributive‐share marker po .